2012
DOI: 10.1073/pnas.1209814109
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human PRMT5:MEP50 complex

Abstract: Protein arginine methyltransferases (PRMTs) play important roles in several cellular processes, including signaling, gene regulation, and transport of proteins and nucleic acids, to impact growth, differentiation, proliferation, and development. PRMT5 symmetrically di-methylates the two-terminal ω-guanidino nitrogens of arginine residues on substrate proteins. PRMT5 acts as part of a multimeric complex in concert with a variety of partner proteins that regulate its function and specificity. A core component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
394
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(417 citation statements)
references
References 44 publications
19
394
1
3
Order By: Relevance
“…These unique features of NTMT1 are in striking contrast to lysine/arginine methyltransferases, such as PRMT5, in which a substrate-binding groove is formed on the surface of these enzymes, and the target histone arginine H4R3 is inserted into a narrow channel to reach the SAM-binding pocket ( Fig. 3C; Antonysamy et al 2012). Therefore, our crystal structures of these NTMT1 ternary complexes described above explain the specificity of NTMT1 in catalyzing α-N-terminal methylation.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These unique features of NTMT1 are in striking contrast to lysine/arginine methyltransferases, such as PRMT5, in which a substrate-binding groove is formed on the surface of these enzymes, and the target histone arginine H4R3 is inserted into a narrow channel to reach the SAM-binding pocket ( Fig. 3C; Antonysamy et al 2012). Therefore, our crystal structures of these NTMT1 ternary complexes described above explain the specificity of NTMT1 in catalyzing α-N-terminal methylation.…”
Section: Resultsmentioning
confidence: 88%
“…(C) The catalytic pocket of PRMT5. PRMT5 (PDB: 4GQB) (Antonysamy et al 2012) is shown in electrostatic surface representation, and the cofactor SAM analog A9145C and the histone H4R3 peptide are shown as green and yellow sticks, respectively. (D) Catalytic mechanism for the α-N-terminal methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the singly methylated species was actually a mixture of peptides Table 1) were methylated by PRMT7 as described in Fig. 3 legend. A-H show PRMT7-catalyzed methylation products of H2B (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) with monomethylation on different arginine residues, and Arg-29 and Arg-31 should be the major methylation sites on H2B. Additionally, the fragmentation pattern for the methylated H2B(23-37)R29K peptide is more consistent with the Arg-31 site of methylation (Fig.…”
Section: Robust Mouse Prmt7 Expressed In Insect Cells Catalyzes the Fmentioning
confidence: 99%
“…Methylation assays were then carried out with the previously characterized substrates GST-GAR, a protein containing the first 148 amino acids of human fibrillarin (5,21), and synthetic peptides derived from the N terminus of human histone H4 (22,23,(25)(26)(27). Using amino acid analysis employing high resolu- tion cation exchange chromatography, we were able to clearly separate MMA, SDMA, and ADMA and capture femtomole levels of methylation products from [ 3 H]AdoMet.…”
Section: Robust Mouse Prmt7 Expressed In Insect Cells Catalyzes the Fmentioning
confidence: 99%
See 1 more Smart Citation